Analisis Faktor-Faktor yang Mempengaruhi Indeks Saham Syariah Indonesia (ISSI) (periode Juni 2012-Mei 2015) - Wahyuningrum, Meylani, Dr. Daryono Soebagiyo, MEc, Nurul Huda, S.Ag., M.Ag (2016)
This study aimed to examine the influence of factors which will affect Indonesia Sharia Stock Index (ISSI) such as inflation, Bank Indonesia Certificates Sharia (SBIS), Exchange (Exchange) Rupiah against the Dollar and Crude Oil Prices World in period June 2012 to May 2015. Methods is descriptive analytic and analysis tools using the Partial Adjustment Model (PAM), while the hypothesis test using Classical assumption test with a significance level of 0.10, or 10 percent. Classic assumption test used in this study include Multicollinearity test, Residual Normality, Heteroskidastity, autocorrelation, and also Goodness Model Specifications Model. Research has been done to produce that Inflation, Exchange Rate (Exchange) Rupiah against the Dollar and Crude Oil Prices World a significant negative effect on Sharia Stock Index Indonesia (ISSI), while that of Bank Indonesia Certificates Sharia (SBIS) positive and significant impact on Stock Index Syariah Indonesia (ISSI). To test Multicolinearity Exchange (Exchange) Rupiah against the Dollar and Bank Indonesia Certificates Sharia (SBIS) there Multicolinearity serious problems, but in other tests such as Residual Normality, Heteroskidastity, autocorrelation, and Goodness Model Specifications Model passed the test. Keywords: Indonesian Sharia Stock Index (ISSI), inflation, Bank Indonesia Certificates Sharia (SBIS), Exchange (Exchange) Rupiah against the Dollar and Crude Oil Prices World.